IMPLEMENTASI 3D PRINTING BETON DAN BAJA PADA DESAIN FABRIKASI DI SEKTOR KONSTRUKSI - Prilita, Nisrina Fahriah Dea; Fuk Jin, Oei (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2024)
The increasing need for development makes humans continue to find more efficient and faster ways. Therefore, technology is also growing rapidly and forcing all sectors to be able to keep up to date so as not to be left behind. The use of 3D Printing is one of the technologies that are beginning to be applied. This 3D Printing technology shows a significant change from conventional construction. The method used in this article is literature review, by collecting previous research literature. This study aims to determine the implementation of 3D Printing on fabrication design in construction. Data obtained from several journals discuss the implementation, advantages, and limitations of 3D Printing in technology, cost and time. Therefore, it is expected to open the views of construction stakeholders to be able to see the potential use of 3D Printing in the construction field.